THEORETICAL ANALYSIS OF MEASURED METOCEAN DATA IN TIME AND FREQUENCY DOMAINS FOR MALAYSIAN WATERS - Duong Vannak, Duong Vannak (2017)
The offshore structures are particularly at risk with any extreme motions initiated by metocean data such as wind speed and wave height. These metocean loads form the critical and prerequisite criteria in the design and operation of offshore structure.